2014
DOI: 10.1515/ijamh-2013-0302
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and hyperinsulinemia in children and adolescents with chronic liver disease: relation to disease severity

Abstract: Dyslipidemia and HI were frequent findings in patients with CLD, which worsened with increased severity of CLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The data providing evidence of higher plasma contents of triglycerides and cholesterol in the current study are also remarkable because hypertriglyceridaemia is usually found in paediatric NAFLD; in some cases, concomitantly with hypercholesterolaemia (Roberts 2005, El-Kabbany et al 2013. Therefore, these results support the previous evidence of the initial stages of NAFLD in the progeny of nutritionally challenged Iberian sows.…”
Section: Discussionsupporting
confidence: 90%
“…The data providing evidence of higher plasma contents of triglycerides and cholesterol in the current study are also remarkable because hypertriglyceridaemia is usually found in paediatric NAFLD; in some cases, concomitantly with hypercholesterolaemia (Roberts 2005, El-Kabbany et al 2013. Therefore, these results support the previous evidence of the initial stages of NAFLD in the progeny of nutritionally challenged Iberian sows.…”
Section: Discussionsupporting
confidence: 90%
“…Chronic liver disease (CLD) is a term used to describe a wide spectrum of disorders, including idiopathic, infectious, genetic, drug-induced, toxin-induced, and autoimmune disorders [1,2]. The common consequence of chronic damage to the liver is cirrhosis [3].…”
Section: Introductionmentioning
confidence: 99%